Investor Analysis: Internal and External Determinants of Earnings Response Coefficient - Viriany Viriany; Monica Salim; Steven Imanuel (Politeknik Siber Cerdika Internasional, 2026)
Background: This study examines the determinants of the earnings response coefficient (ERC) in Indonesian commodity, chemical, and construction sectors. Objective: To identify factors affecting the earnings response coefficient (ERC) in Indonesian listed companies during 2021–2023. Methods: Purposive sampling was used to obtain 22 firms and a total of 66 observations that met the criteria. The following inclusion and exclusion criteria were applied: (1) companies continuously listed on the IDX in the subsectors of basic chemicals, agrochemicals, specialty chemicals, and building materials during 2021–2023; (2) companies issuing annual reports and financial statements that have been fully audited; (3) companies with stock price data available throughout the event window; (4) companies reporting net profit data for at least two consecutive years; (5) companies not suspended from trading during the observation period; and (6) companies with non-extreme or non-outlier data. Based on these criteria, 22 companies were selected, resulting in 66 observations across the financial years. The Common Effect Model (CEM) was selected based on the Chow, Hausman, and Lagrange Multiplier (LM) tests. Results: Regression analysis showed that earnings persistence had a significant negative effect, while growth opportunities had a significant positive effect. Meanwhile, default risk, systematic risk, and accounting conservatism did not affect the earnings response coefficient. Conclusion: Growth opportunities significantly increase the earnings response coefficient, while default risk, profit persistence, and accounting conservatism have no significant effect. These findings indicate that investors place greater emphasis on growth prospects than on risk-related indicators when responding to earnings information.